1980
DOI: 10.1029/jb085ib07p03690
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cooling rate on the intensity of weak‐field trm in single‐domain magnetite

Abstract: The effect of cooling rate on the intensity of low‐field thermoremanent magnetization (TRM) in uniaxial, single‐domain magnetite is calculated, using both numerical and analytical techniques. These calculations indicate that when a single‐domain assemblage is cooled much more slowly than in a typical laboratory experiment, it can remain magnetically unblocked and in thermal equilibrium with an external field at temperatures significantly lower than the ‘laboratory’ blocking temperature. Owing to the rapid rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
155
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 6 publications
18
155
0
3
Order By: Relevance
“…Single domain (SD) theory predicts ∼3-7% change in magnetization per one order of magnitude change in cooling rate, with a slower cooling resulting in stronger magnetization (Dodson and McClelland-Brown, 1980;Halgedahl et al, 1980). This should correlate to the same amount of bias in paleointensity estimates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single domain (SD) theory predicts ∼3-7% change in magnetization per one order of magnitude change in cooling rate, with a slower cooling resulting in stronger magnetization (Dodson and McClelland-Brown, 1980;Halgedahl et al, 1980). This should correlate to the same amount of bias in paleointensity estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The horizontal error bar indicates the plausible range of the cooling rate; see the text for a discussion). The dashed line represents the theoretical paleointensity overestimate (Halgedahl et al, 1980) with respect to the mean VDM calculated from the PINT data.…”
Section: Cooling Rate Effect On Plutonic Paleointensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dodson and McClelland-Brown (1980) showed that blocking temperatures of single domain grains are related to the cooling rate and the TRM acquired at different cooling rates in the same field might differ significantly. This will bias the estimation of paleointensity (Halgedahl et al, 1980). In order to obtain the most accurate results, we applied a cooling rate correction for each specimen after the paleointensity experiment.…”
Section: Anisotropy Correctionmentioning
confidence: 99%
“…A remanence tensor for anisotropy corrections was calculated from TRMs acquired in six orthogonal positions, or with anhysteretic magnetizations acquired in nine positions. Corrections for cooling rate effects were done assuming a logarithmic relationship between TRM overestimation from ratios of laboratory versus original cooling rates (20), and cooling time from 500°C to 200°C approximations of 0.1 h, 3.7 h, and 6 h for the laboratory-fast, laboratoryslow, and ancient cooling times. In all experiments, the field during "in-field cooling" in the oven was 60 μT.…”
Section: Significancementioning
confidence: 99%